Humanista a határon. - Sebők, Marcell, author.
1 online resource (ix, 257 pages)
Keywords: "A Humanist on the Frontier explores the remarkable life of Sebastian Ambrosius, a sixteenth-century Lutheran minister and intellectual from Késmárk in present-day Slovakia, formerly on the borderland of the Kingdom of Hungary. Through an examination of Ambrosius' publications and correspondence, this book throws new light on the dynamics of urban communities in Upper Hungary, communication within the humanist Republic of Letters in both Central European and wider European networks, and ecclesiastical controversies. Adopting methods of microhistory and cultural history, it also reconstructs Ambrosius' life by positioning him in various contexts that trace his relationship to, and interpretations of, themes of power, tradition, vocation, communication and identity. This book is essential reading for scholars and students of early modern European history, as well as those interested in microhistory, cultural history, and the Republic of Letters"--